2014
DOI: 10.1021/nl501803s
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Silicon Oxide Memory

Abstract: Oxide-based two-terminal resistive random access memory (RRAM) is considered one of the most promising candidates for next-generation nonvolatile memory. We introduce here a new RRAM memory structure employing a nanoporous (NP) silicon oxide (SiOx) material which enables unipolar switching through its internal vertical nanogap. Through the control of the stochastic filament formation at low voltage, the NP SiOx memory exhibited an extremely low electroforming voltage (∼ 1.6 V) and outstanding performance metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 29 publications
2
66
0
Order By: Relevance
“…In general a high bias is applied to the system with a compliance current set to prevent complete breakdown [56]. For nanogap electrodes on SiO2, the forming voltage has been found to be 12 V for a 15 nm gap [28], 29 V for a 50 nm gap [33] and 1.6 V for 2 nm gaps [57]. These values would indicate a dielectric strength of SiO2 in the range 6-8 MV cm -1 , a value on par with those reported in the literature [58].…”
Section: Forming Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…In general a high bias is applied to the system with a compliance current set to prevent complete breakdown [56]. For nanogap electrodes on SiO2, the forming voltage has been found to be 12 V for a 15 nm gap [28], 29 V for a 50 nm gap [33] and 1.6 V for 2 nm gaps [57]. These values would indicate a dielectric strength of SiO2 in the range 6-8 MV cm -1 , a value on par with those reported in the literature [58].…”
Section: Forming Stepmentioning
confidence: 99%
“…The only difference in the reported mechanisms is that for nanogap dimension change due to material migration switching, a sweep about the set voltage (e.g. +10 V → -1 V, [54] or +9 V → + 3 V [53] ) is employed, whereas for oxide switching, a pulse at the set voltage suffices [28], [31], [33], [55], [57].…”
Section: Forming Stepmentioning
confidence: 99%
“…After decades of intensive research, many inorganic oxides, 7 polymers 8 and small molecules 9,10 have been found to exhibit multilevel resistive switching behaviours and are thus considered candidate active materials for multilevel RRAMs. However, to enable industrial use, RRAM devices must show good reproducibility, including a high multilevel memory device yield and narrow distribution of OFF/ON1/ON2 switching voltages.…”
mentioning
confidence: 99%
“…Unlike some types of memristors, the a − Si memristors require high write voltages. For an example, the nanoporous SiO x based devices have very low forming voltages (∼ 1.4V) [35]. Having smaller operating voltages in memristive crossbars require sophisticated sensing mechanisms.…”
Section: Memristors As Synapses and Neuronsmentioning
confidence: 99%